Legal Construction of Government Agency Asset Certification Regarding Land Rights Formerly Under Dutch Control - Jacki Mahendra; Mohammad Hamidi Masykur; R. Imam Rahmat Sjafi'i (Danadyaksa, 2025)
An important aspect of optimal management of state assets includes aspects of securing state assets. The form of state asset security measures can be through certification activities for land plots spread throughout the territory of Indonesia. Normatively, "Law of the Republic of Indonesia Number 1 of 2004 concerning State Treasury instructs that state/regional property in the form of land controlled by the Central/Regional Government must be certified in the name of the government of the Republic of Indonesia/the relevant regional government." In its development, it turned out that there were assets owned by government agencies that had the status of objects of Control of Fixed Assets Owned by Individual Dutch Citizens" or Dutch Legal Entities (P3MB). Normatively, the P3MB land certification process has special regulatory characteristics, namely the priority scale of granting rights and payment of compensation to the State through the Sale and Purchase. Of course, this is. However, what the author needs to highlight here is that there is no subject of Prospective Recipients of Rights in the Government/Government Agency group. In addition, problems also occur regarding the purchase mechanism up to the process of transferring rights by Government Agencies, which should be a single entity with the State itself.